Case Report: Vanishing bile duct syndrome in Hodgkin’s lymphoma: a case highlighting jaundice and lymphadenopathy as early clues - Ma, Shiyu; Cai, Dali; Miao, Yuan; Deng, Baocheng; Yan, Xiaojing; Gao, Ran (Frontiers in Immunology, 2025)
Vanishing bile duct syndrome is a specific pathologic process characterized by ductopenia and intrahepatic cholestasis, which may be a unique paraneoplastic syndrome of Hodgkin’s lymphoma with an unfavorable prognosis. We report a 34-year-old woman with acute jaundice and lymphadenopathy, which was subsequently confirmed to be Hodgkin’s lymphoma with concurrent vanishing bile duct syndrome based on a liver biopsy. The patient agreed to combination chemotherapy with brentuximab vedotin and achieved a complete response. Liver function recovered within 4 months. This article reviews the literature and provides insight for addressing similar clinical challenges.